ANTICIPATING AND MANAGING THE PSYCHOLOGICAL COST OF CIVIL LITIGATION - Keet, Michaela; Heavin, Heather; Sparrow, Shawna (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
Despite growing national attention on the costs of accessing justice, surprisingly little information has been collected about the psychological ‘costs’ of engaging in litigation. This article summarizes the health and psychology literature, to present a picture of the impact that litigation can have on litigants’ health, state of mind, life goals and social relationships. Set against professional obligations embedded in the lawyer’s role, we assert that awareness of the negative impacts of legal processes on the emotional and psychological functioning of clients is important. With greater awareness, lawyers can better assess the value of litigation, prepare their clients (and themselves) for litigation stress, and, where appropriate, take preventative actions to minimize the negative aspects of the litigation experience. With that in mind, we identify positive solution-oriented responses to preventing, reducing and alleviating litigation stress. These strategies focus on client-centred communication, supports and planning.